2017
DOI: 10.1097/fjc.0000000000000462
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac GPCR–Mediated EGFR Transactivation: Impact and Therapeutic Implications

Abstract: G protein-coupled receptors (GPCR) remain primary therapeutic targets for numerous cardiovascular disorders, including heart failure (HF), due to their influence on cardiac remodeling in response to elevated neurohormone signaling. GPCR blockers have proven to be beneficial in the treatment of HF by reducing chronic G protein activation and cardiac remodeling, thereby extending the lifespan of HF patients. Unfortunately this effect does not persist indefinitely, thus next generation therapeutics aim to selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 77 publications
0
15
0
1
Order By: Relevance
“…This is consistent with reports from experimental animal models in which the conditional overexpression (Sysa-Shah et al 2012) or mutation of epidermal growth factor receptor 2 (ErbB2) (Ozcelik et al 2002) in mice induces hypertrophic cardiomyopathy. An additional factor could be attributed to the ability of an expanding number of G-protein coupled receptors (GPCRs) that can transactivate EGFR in cardiac tissue (Grisanti et al 2017). GPCRs constitute the largest receptor superfamily known, and because of its wide-ranging role in cardiovascular disorders, greater than 40% of all current therapeutics are targeted to GPCRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with reports from experimental animal models in which the conditional overexpression (Sysa-Shah et al 2012) or mutation of epidermal growth factor receptor 2 (ErbB2) (Ozcelik et al 2002) in mice induces hypertrophic cardiomyopathy. An additional factor could be attributed to the ability of an expanding number of G-protein coupled receptors (GPCRs) that can transactivate EGFR in cardiac tissue (Grisanti et al 2017). GPCRs constitute the largest receptor superfamily known, and because of its wide-ranging role in cardiovascular disorders, greater than 40% of all current therapeutics are targeted to GPCRs.…”
Section: Discussionmentioning
confidence: 99%
“…GPCRs constitute the largest receptor superfamily known, and because of its wide-ranging role in cardiovascular disorders, greater than 40% of all current therapeutics are targeted to GPCRs. Thus, in the diabetes context, a variety of GPCR ligands may activate their receptors (e.g., adenosine, adrenergic, aldosterone, angiotensin II, bradykinin, δ-opioid, endothein-1, muscarinic, prostaglandin E2, protease-activated, sphingosine-1phosphate, urotensin II) (Grisanti et al 2017), which in turn, can transactivate EGFR and induce cardiomyopathies. Even in endotoxemic heart failure, lipopolysaccharidemediated EGFR transactivation has been implicated (Sun et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the new suggested interactions in dashed lines, some studies with other cell types have shown that KN93 increases the MEK12/ERK1/2 activity through EGFR activation [ 65 ], but this activation is not through Ras/Raf1 [ 66 ] and directly influences ERK1/2 activity. Also, there are several studies which confirm the transactivation of other pathways like EGFR during β-adrenergic receptor activation and their Ras-independent influence on ERK1/2 activity [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that G-protein-coupled receptors (GPCRs) and Src are involved in ligand-independent EGFR transactivation [23,24]. In this study, we investigated the role of Src in ligand-independent EGFR activation.…”
Section: Resultsmentioning
confidence: 99%